2015
DOI: 10.2196/ijmr.4287
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Organ Donation Information Campaigns in Germany: A Facebook Based Online Survey

Abstract: BackgroundThe German transplantation system is in a crisis due to a lack of donor organs. Information campaigns are one of the main approaches to increase organ donation rates. Since 2012, German health insurance funds are obliged by law to inform their members about organ donation. We raised the hypothesis: The willingness to sign a donor card rises due to the subsequent increase of specific knowledge by receiving the information material of the health insurance funds.ObjectiveThe objective of the study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The average age of the sample was quite low – only 23 years old. This finding is comparable to studies in other university settings nationally and worldwide 10,15,16. The low mean age of respondents could be influential in the shaping of response patterns, as this age group presents with different values regarding organ donation compared to older populations.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The average age of the sample was quite low – only 23 years old. This finding is comparable to studies in other university settings nationally and worldwide 10,15,16. The low mean age of respondents could be influential in the shaping of response patterns, as this age group presents with different values regarding organ donation compared to older populations.…”
Section: Discussionsupporting
confidence: 84%
“…Studies assessing a sample's general knowledge about organ donation 1,2,11,13,14,16,17 have demonstrated misinformation on the same subjects as the control group in our study. Terbossen et al 17 showed that German medical students who did not carry a donor's card feared feeling pain during organ extraction procedures.…”
Section: Discussionmentioning
confidence: 47%
“…This method was reported to be effective among the study participants in Germany. [ 38 ] Another approach was the Gerundium program in Hungary where medical students were trained to give lectures to high schools and colleges about organ and tissue donation. [ 39 ] Furthermore, leveraging the social media platform to reach the youth's awareness can also be effective.…”
Section: Discussionmentioning
confidence: 99%
“…To promote and improve the public awareness on organ donation and transplantation, educational campaign is a vital approach. Studies showed that the more the public is informed about the various aspect of organ donation and transplant, the higher the public awareness 29,30) .…”
Section: Key Factors To Increase Cadaveric Kidney Donationmentioning
confidence: 99%